Incidence of rheumatoid arthritis in Austria: a prospective population-based cohort study in a federal province - Tanja A Stamm; Valentin Ritschl; Judith Sautner; Rudolf Puchner; Alois Alkin; Herwig Pieringer; Lorenz Balcar; Yvonne Rammer; Sabine Schumacher (RMD Open)
Objective When it comes to prospective studies on the incidence of rheumatoid arthritis (RA), the Norfolk study from 1994 is still frequently cited as prospective incidence data by many countries lacking comprehensive RA registries, including Austria. The aim of this study was, therefore, to gather robust data on the incidence of RA among Austrian adults for the first time.Methods All Upper Austrian rheumatologists reported newly diagnosed RA patients with symptom onset between 2016 and 2018, together with demographic data, laboratory and radiographic results. Cases still unclear at the end of 2018 were tracked in an extended observation period until 2023.Results In total, 701 RA cases were reported. 583 complete patient datasets were analysed. In all 551 individuals with a mean age of 60.2 (±14.2) years, 359 (65.2%) being females, the diagnosis of RA was ascertained clinically by a rheumatologist, optionally applying RA-classification criteria. Across all 3 years, the annual RA incidence rate was 14.9/100 000 (95% CI 12.9 to 17.3), ranging from 20.0/100 000 (95% CI 17.6 to 22.7) in 2016 to 13.5/100 000 (95% CI 11.5 to 15.7) in 2017 and 11.3/100 000 (95% CI 9.5 to 13.3) in 2018. The incidence was highest in individuals >65 years (21.6/100 000, 95% CI 16.4 to 27.9). Women had a higher RA incidence (18.1/100 000, 95% CI 14.9 to 21.7) than men (10.4/100 000, 95% CI 8.0 to 13.3).Conclusions This study provided prospective population-based data on the incidence of RA in Austrian adults for the first time. Incidence rates were comparable with other European countries. Compared with the Norfolk study, we found lower rates in both genders, more pronounced in females, however.